An Exploration of Digital Sentiment and Individual Knowledge as Predictors of Tuberculosis Vaccination Decisions: A Social Media and Survey-Based Study - Desy Eliana; Wicaksono Yuli Sulistyo; Muhamad Rosidin (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
Tuberculosis (TB) remains a major communicable disease in Indonesia with consistently high incidence rates, making vaccination a key preventive strategy. However, resistance toward the TB vaccine persists due to limited public knowledge and the influence of negative sentiments circulating on social media. This study aimed to examine the relationship between individual knowledge and vaccination decisions, while also analyzing public sentiment toward the TB vaccine on social media as an early indicator for designing epidemiological interventions. A mixed-methods approach was applied, combining a cross-sectional survey involving 100 respondents—which assessed TB knowledge, exposure to vaccine-related social media content, and BCG vaccination status—with sentiment analysis using the Naive Bayes algorithm on 26 social media posts from Twitter, TikTok, and Instagram. Logistic regression results indicated that higher knowledge about TB (OR = 1.76, 95% CI: 1.17–2.67) and increased exposure to social media content (OR = 1.46) were significantly associated with positive vaccine decision-making. Among the analyzed posts, 53.8% conveyed positive sentiment, 26.9% were neutral, and 19.2% expressed negative views, with positive sentiments predominantly found in educational content shared by healthcare professionals. These findings highlight the alignment between individual knowledge and digital public sentiment in influencing vaccination decisions, underscoring the importance of integrating health education and digital data monitoring in TB prevention effort.